2010
DOI: 10.1002/poc.1658
|View full text |Cite
|
Sign up to set email alerts
|

Quantum catalysis? A comment on tunnelling contributions for catalysed and uncatalysed reactions

Abstract: Appreciation for the contribution of nuclear quantum effects (NQEs) to chemical reactivity predates transition‐state theory (TST). Quantum corrections to rate constants for the reactions catalysed by lactate dehydrogenase (LDH) and formate dehydrogenase (FDH) and the same reactions in water are estimated by Bell's one‐dimensional approximate method and give tunnelling contributions to catalysis of 1.6 and 0.95, respectively. Published results for NQEs, including both tunnelling and zero‐point energies, estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
13
0
4
Order By: Relevance
“…[80][81][82] A second example is the long-standing debate about the importance of dynamic effects in enzymatic reactions and about the idea that enzymes may have evolved to optimize a particular nuclear motion that facilitates reaching the catalytically relevant transition state. [145][146][147][148][149] There are many facets to this issue, which can be addressed through simulations once the "dynamic effects" have been properly defined. [149] In the framework of transition state theory (TST), dynamic nonequilibrium effects due to protein motion will cause the transmission coefficient to be smaller than unity; however, computational studies of various enzymes have revealed only slight deviations from unity, by factors of 3 or less.…”
Section: Conceptsmentioning
confidence: 99%
“…[80][81][82] A second example is the long-standing debate about the importance of dynamic effects in enzymatic reactions and about the idea that enzymes may have evolved to optimize a particular nuclear motion that facilitates reaching the catalytically relevant transition state. [145][146][147][148][149] There are many facets to this issue, which can be addressed through simulations once the "dynamic effects" have been properly defined. [149] In the framework of transition state theory (TST), dynamic nonequilibrium effects due to protein motion will cause the transmission coefficient to be smaller than unity; however, computational studies of various enzymes have revealed only slight deviations from unity, by factors of 3 or less.…”
Section: Conceptsmentioning
confidence: 99%
“…Ein Beispiel hierfür ist die Zwei-Zustands-oder Viel-Zustands-Reaktivität [142] unter Einbeziehung verschiedener Spinzustände (und mit Übergängen zwischen den Potentialflächen von Zuständen unterschiedlicher Multiplizität). [145][146][147][148][149] Bei dieser Thematik gibt es viele Aspekte, die durch Simulationen untersucht werden kçnnen, sobald die postulierten "dynamischen Effekte" sauber definiert sind. Ihre mechanistische Bedeutung wurde in kombinierten experimentellen und theoretischen Untersuchungen erkannt [142] und ist seither sowohl in der homogenen Übergangsmetallkatalyse [61,[142][143][144] als auch in der Biokatalyse mit Metallproteinen [80][81][82] fest etabliert.…”
Section: Konzepteunclassified
“…Ein zweites Beispiel ist die lange währende Debatte über die Bedeutung dynamischer Effekte in enzymatischen Reaktionen und über das Konzept, dass Enzyme im Laufe der Evolution bestimmte Kernbewegungen optimiert haben kçnnten, um den katalytisch relevanten Übergangszustand leichter zu erreichen. [145][146][147][148][149] Bei dieser Thematik gibt es viele Aspekte, die durch Simulationen untersucht werden kçnnen, sobald die postulierten "dynamischen Effekte" sauber definiert sind. [149] Im Rahmen der Theorie des Übergangszustands ("transition state theory", TST) bewirken dynamische Nichtgleichgewichtseffekte aufgrund der Proteinbewegung eine Verringerung des Trans-.…”
Section: Konzepteunclassified
See 1 more Smart Citation
“…The current controversy is more a question of whether tunneling contributes to enzyme catalysis; to enhance rates directly as a result of quantum nuclear effects (primarily tunneling) as compared to what occurs in solution in the enzyme's absence. However, there appears to be little or no evidence supporting catalytic enhancement (Williams, 2010). In spite of this, another important question is whether enzymes have evolved by natural selection based on enhancing the tunneling phenomenon itself.…”
Section: Quantum Microbiology 45mentioning
confidence: 99%